Implementasi Aplikasi Microsoft Power BI Untuk Pengolahan dan Visualisasi Data Strategis Pemilu 2024 - Bukran, Bukran; Switrayana, I Nyoman; Kayohana, Ketut Widya; Alfiansyah, Muhamad Wisnu (Jurnal Pengabdian Pada Masyarakat IPTEKS, 2023)
This research focuses on the use of Microsoft Power BI by the DPD PKS Lombok Tengah Data Team in processing and visualizing strategic data for the 2024 election to formulate an effective winning strategy. This research begins with a brief background that highlights the increasing importance of data-based decision making in political campaigns. The primary objective was to assess the impact of implementing Microsoft Power BI in improving the team's analytical capabilities and informing strategic decisions for electoral success. The research utilized a comprehensive methodology involving training sessions and practical application of Microsoft Power BI. The results showed significant improvements in the team's proficiency in data analysis and visualization. Achievements include the successful integration of Microsoft Power BI into the election strategy formulation process, empowering the team to make informed decisions based on in-depth data visualization. This research contributes to the ever-evolving world of political campaigns by demonstrating the practical benefits of implementing advanced data processing tools for election success.